ImmunoPET: Antibody-Based PET Imaging in Solid Tumors - Manafi-Farid, Reyhaneh; Ataeinia, Bahar; Ranjbar, Shaghayegh; Jamshidi Araghi, Zahra; Moradi, Mohammad Mobin; Pirich, Christian; Beheshti, Mohsen (Frontiers in Medicine, 2022)
Immuno-positron emission tomography (immunoPET) is a molecular imaging modality combining the high sensitivity of PET with the specific targeting ability of monoclonal antibodies. Various radioimmunotracers have been successfully developed to target a broad spectrum of molecules expressed by malignant cells or tumor microenvironments. Only a few are translated into clinical studies and barely into clinical practices. Some drawbacks include slow radioimmunotracer kinetics, high physiologic uptake in lymphoid organs, and heterogeneous activity in tumoral lesions. Measures are taken to overcome the disadvantages, and new tracers are being developed. In this review, we aim to mention the fundamental components of immunoPET imaging, explore the groundbreaking success achieved using this new technique, and review different radioimmunotracers employed in various solid tumors to elaborate on this relatively new imaging modality.